الانزياح التركيبي وجمالياته الشعرية عند "أبي حمو موسى الزياني" : "مقاربة في أسلوبية التركيب الشعري " - بوزيدي, سليم (Revues faculté des lettres et des langues; No 18 (2016): مجلة كلية الآداب واللغات, 2016)
يركز هذا البحث على دراسة ظاهرة الانزياح الأسلوبي في التراكيب الشعرية عند أبي حمو موسى الزياني، من حيث أَثَرُهُ في التراكيب الاسمية والفعلية، وفي نسيج العمل الأدبي ككل، فعن طريق الانزياح تتحقق للنص أدبيته، وتأثيره في المتلقي. وفيه حاولنا استجلاء أشكال الانزياح، وجمالياته في ضوء المنهج الأسلوبي الحديث. وقد تنوع الانزياح فيها بين التقديم والتأخير، والحذف، وقد أد دورها في بيان المعاني وتوضيحها، وهذا ما يكشف عن تعدد تقنيات النظم وأساليبه الفنية، التي تفرد بها الشاعر أبو حمو موسى الزياني.         The current research study revolves around pinpointing the stylistic deviations in the poems of Abu Hammou Moussa Azyiati in view of their impact both on the nominal and verbal constituents and on the literary work in its entity. The role of deviation is twofolds: it is fundamentally through deviation that the text’s literatures along with the impact thereof on the recipient are accomplished. And we try to dwelve into the different facets of deviation and its aesthetics drawing on the tenets of the modern trend of the stylistic approach. Deviation is multi faceted in fronting backing  and deletion. Put together, these features have fulfilled their role in meaning clarity. This, by implication, reveals the multi-dimensional poetic techniques and aesthetic styles which impart uniqueness to Abu Hammou Moussa Aziyati’s poems.